Can AI Reduce Healthcare Administrative Costs? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The healthcare industry is grappling with soaring administrative costs, which account for a significant portion of total healthcare spending. In the United S...
Keywords: Healthcare Administration and AI; Reduce; Healthcare; Administrative; Artificial Intelligence; Machine Learning; Patient Care